1977
DOI: 10.1038/bjc.1977.237
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of prostaglandins as bone-resorbing agents by renal cortical carcinoma in culture

Abstract: Summary.-Fragments of human renal carcinoma tissue have been co-cultured with mouse calvaria. In 9/13 cases significant bone resorption occurred whilst in no case did control kidney cause significant resorption. When bone resorption did occur, it could be reduced by inclusion of indomethacin in the culture medium. In some cases when theophylline was included in culture medium to prevent cyclic AMP breakdown, there was enhancement of tumour-induced bone resorption. Control studies without tumour showed that non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

1978
1978
1991
1991

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…A crucial study carried out at that time, however, was that of Powell et al (1973) who found in several patients with humoral hypercalcaemia whose tumour extracts resorbed bone in vitro, that PTH could not be detected either in plasma or in tumour extracts, despite the use of a wide range of PTH antisera directed against several different parts of the molecule. Other work, including our own (Atkins et al, 1977), showed that tumours could produce bone resorbing activity in vitro which was due to something other than PTH.…”
Section: Hypercalcaemia I N Cancermentioning
confidence: 65%
“…A crucial study carried out at that time, however, was that of Powell et al (1973) who found in several patients with humoral hypercalcaemia whose tumour extracts resorbed bone in vitro, that PTH could not be detected either in plasma or in tumour extracts, despite the use of a wide range of PTH antisera directed against several different parts of the molecule. Other work, including our own (Atkins et al, 1977), showed that tumours could produce bone resorbing activity in vitro which was due to something other than PTH.…”
Section: Hypercalcaemia I N Cancermentioning
confidence: 65%
“…It may also be postulated that by inhibiting the prostaglandin-associated bone-resorbing activity oftumours (Strausser & Humes, 1975;Powles et al, 1976;Atkins et al, 1977) indomethacin restricts the calcium available to the neoplastic cells (Strausser & Humes, 1975). However, while i.m.…”
Section: Effect Of Tumour-and Indomethacin On Antibody Synthesismentioning
confidence: 99%
“…THE AMOUNTS OF PROSTAGLANDINS extracted from various tumours, notably from human carcinomas of the breast (Bennett et al, 1975Powles et al, 1976), large intestine (Bennett et al, 1977) and kidney (Atkins et al, 1977) and from certain experimental neoplasms (Powles et al, 1 973;Tashjian et al, 1974;Galasko, 1.976;Galasko & Bennett, 1976) are usually greater than from the corresponding normal tissues. Prostaglandins and other lessclearly defined "tumour-associated" products may be involved in the establishment and growth of metastases in bone and possibly in other sites (Carter, 1978;Bennett, 1979).…”
mentioning
confidence: 99%